Stimulation of DNA repair in saccharomyces cerevisiae by ginkgo biloba leaf extract - Marques, Filipe (2011)
Many extracts prepared from plants traditionally used for medicinal applications contain a variety of phytochemicals with antioxidant and antigenotoxic activity. In this work we measured the DNA protective effect of extracts of Ginkgo biloba leaves from oxidative stress using Saccharomyces cerevisiae as experimental model. The extract improved viability of yeast cells under oxidative stress imposed by hydrogen peroxide. In accordance with previous reports on antioxidant properties of G. biloba extracts, pre-incubation of yeast cells promoted a decrease in intracellular oxidation. We assessed DNA damage by our recently developed yeast comet assay protocol. Upon oxidative shock, DNA damage decreased in a dose-dependent manner in experiments of pre-incubation and simultaneous incubation with the extract, indicating a direct protective effect. In addition, the extract improved DNA repair rate following oxidative shock as measured by faster disappearance of comet tails. This suggests that the extract stimulates the DNA repair machinery in its DNA protective action in addition to directly protect DNA from oxidation. The observed DNA repair depends on the DNA repair machinery since no DNA repair was observed under restrictive conditions in a conditional mutant of the CDC9 gene (Accession No. Z74212), encoding the DNA ligase involved in the final step of both nucleotide and base excision repair.